A bibliometric analysis of extracellular vesicles as drug delivery vehicles in disease treatment (2010–2024) - Wuli Guo; Qi Shu; Lina Gao; Na Gao; Zhen Wang; Wenjing Wei; Yuhan Zhang; Ting Huyan; Qi Li (Extracellular Vesicle)
To comprehensively summarize the progress of utilizing extracellular vesicles (EVs) as drug delivery vehicles in disease treatment, bibliometric and visualization tools were employed to analyze and exhibit the key information from 6515 literatures that collected by searching “drug delivery” and “extracellular vesicles”, as well as “drug delivery” and “exosomes” as the keywords in Web of Science Core Collection. The obtained articles are from 90 countries/regions, 3343 institutions, 17,989 authors, and 591 journals. Among them, the “nanoparticles”, “cancer” and “biomarkers” are the keywords with the highest frequency. According to experimental articles, EVs are mainly used in the treatment of cancer as drug vehicles.